Penyelenggaraan Pariwisata Syariah di Hotel Natama - Ahmatnijar, Indri Lestari Pasaribu & Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The results showed that the implementation of sharia principles at Natama Syariah Hotel is operationally in accordance with the DSN-MUI Fatwa Number: 108 / DSN-MUI / X / 2016 concerning the Implementation of Tourism Based on Sharia Principles. However, administratively it is not in accordance with the DSN-MUIN Fatwa Number: 108 / DSN-MUI / X / 2016 concerning the Implementation of Tourism Based on Sharia Principles. Because in practice Hotel Natama has not made the security of wifi facilities so that it can still access pornographic things and Hotel Natama has not received a halal certificate from the MUI. However, Hotel Natama has provided halal food and beverage ingredients even though it has not received a halal certificate. The inhibiting factors are the monitoring and evaluation factors by the DSN-MUI that are not yet optimal, the socialization factor about sharia hotels that is not optimal, the trust factor, where the hotel fully trusts guests to comply with all regulations at the hotel. Based on the description above, the thing that must be done immediately is to make wifi security and continue processing the halal certificate from the Indonesian Ulema Council, to guarantee halal food and drinks provided by hotels labeled as Sharia.